LARGER MAMMALS - Sally Soo, Kaicheen; Mohd Azlan, Jayasilan (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd, 2024)
Given the widespread loss of old-growth forests throughout the tropics, it is likely that secondary forests will be a crucial factor in the preservation of biodiversity. An increase in secondary forests has been observed in the tropics where it is believed to cover approximately 50% of the remaining tropical rainforests.